The effect of negative remodeling on fractional flow reserve after cardiac transplantation. (15th August 2017) - Fearon, William F.; Felix, Robert; Hirohata, Atsushi; Sakurai, Ryota; Jose, Powell O.; Yamasaki, Masao; Nakamura, Mamoo; Fitzgerald, Peter J.; Valantine, Hannah A.; Yock, Paul G.; Yeung, Alan C.
Abstract: Background: Negative remodeling is a common occurrence early after cardiac transplantation. Its impact on the development of myocardial ischemia is not well documented. The aim of this study is to investigate the impact of negative remodeling on fractional flow reserve after cardiac transplantation. Methods: Thirty-four cardiac transplant recipients underwent intravascular ultrasound (IVUS) and fractional flow reserve (FFR) assessment soon after transplantation and one year later. Patients were divided into those with and without negative remodeling based on IVUS, and the impact on FFR was assessed. In the 19 patients with negative remodeling, there was no significant change in plaque volume (119.3 ± 82.0 to 131.3 ± 91.2 mm 3, p = 0.21), but vessel volume (775.6 ± 212.0 to 621.9 ± 144.1 mm 3, p < 0.0001) and lumen volume (656.3 ± 169.1 to 490.7 ± 132.0 mm 3, p < 0.0001) decreased significantly and FFR likewise decreased significantly (0.88 ± 0.06 to 0.84 ± 0.07, p = 0.04). In the 15 patients without negative remodeling, vessel volume did not change (711.7 ± 217.6 to 745.7 ± 198.5, p = 0.28), but there was a significant increase in plaque volume (126.8 ± 88.3 to 194.4 ± 92.7, p < 0.001) and a resultant significant decrease in FFR (0.89 ± 0.05 to 0.85 ± 0.05, p = 0.01). Conclusion: Negative remodeling itself, without any change in plaque volume can cause a significant decrease in fractional flow reserve after cardiac transplantation and appears to be another possible mechanism for myocardial ischemia.